Lower expression of miR-218 in human breast cancer is associated with lymph node metastases, higher grades, and poorer prognosis - Fereshteh Ahmadinejad; Seyed Javad Mowla; Mohammad-Amin Honardoost; Mostafa Gholami Arjenaki; Mohammad Moazeni-Bistgani; Soleyman Kheiri; Hossein Teimori (Tumor Biology, 2017)
Breast cancer is considered as the most prevalent malignancy in women worldwide. Despite emergence of several prognosticators for better management of patients, there are still limitations for their clinical application due to the complexity of breast tumors, and therefore, new biomarkers for better prognosis of clinical outcomes would be of the great essence. MicroRNAs are highly conserved small non-coding regulatory RNAs involved in post-transcriptional regulating of gene expression during different cellular mechanisms. Accumulating studies suggest that miR-218 plays a multifunctional role in various cancer types and different stages. Here, to address prognostic significance of miR-218 in breast cancer, we investigate the expression profile of miR-218 and B-cell-specific Moloney murine leukemia virus integration site 1 ( BMI1 ) gene, as one of the putative targets of miR-218, in 33 paired breast tumors and their adjacent normal tissues with respect to the clinicopathological features of patients using quantitative real-time polymerase chain reaction. The correlation of both miR-218 and BMI1 gene expression with overall survival of breast cancer patients was also examined recruiting OncoLNC data portal. Finally, to better understand biological function of miR-218 in breast cancer, we performed in silico Gene Ontology and signaling pathway enrichment analysis on miR-218 targetome. According to our data, significant elevation of the expression of miR-218 and downregulation of BMI1 were observed in clinical breast cancer specimens compared with normal tissues ( p  < 0.0001). The lower expression of miR-218 was associated with lymph node metastases, higher grades, and poorer prognosis (logrank p  = 0.00988), whereas no significant difference in overall survival was observed between patients with higher and lower expression of BMI1 (logrank p  = 0.254). These findings suggest that miR-218 expression profiling might be clinically applicable as a prognostic biomarker in breast cancer. In addition, our in silico enrichment analyses revealed that the association of miR-218 expression with breast cancer prognosis might be through its involvement in endocytosis and gap junction biological pathways.